Opening Pandora's bait box: a potent vector for biological invasions of live marine species. Issue 1 (15th October 2015) - Fowler, Amy E.; Blakeslee, April M. H.; Canning‐Clode, João; Repetto, Michele F.; Phillip, Anne M.; Carlton, James T.; Moser, Fredrika C.; Ruiz, Gregory M.; Miller, A. Whitman
Abstract: Aim: For over 80 years, the Maine baitworm trade has shipped live polychaete worms and packing algae 'wormweed' to distributors world‐wide, while also consistently transferring a wide diversity and abundance of hitchhiking organisms of all life stages to numerous recipient communities. Here, we investigate this potent, yet underestimated, invasion vector using an important recipient region (the Mid‐Atlantic) to examine the stepwise species transfer and survival along four stages of the vector. Location: Maine and Mid‐Atlantic region (New Jersey, Delaware, Maryland, Virginia and North Carolina), USA. Methods: We quantified taxonomic identities and abundances of organisms associated with packing algae at four stages along the vector pathway during summer 2011: (1) Maine source habitats; (2) bait boxes from Maine distributors; (3) bait boxes from distributors in five Mid‐Atlantic States; and (4) bait bags from retailers in five Mid‐Atlantic States. We also examined functional diversity based on significant physical and life history characteristics and assessed genetic diversity for two common hitchhiking snail species. Results: We identified 17, 798 live macro‐organisms across 58 taxa, including marine macro‐invertebrates, macroalgae, vascular plants and semi‐terrestrial or aquatic invertebrates, present in bait boxes and bags. In all measures of diversity and abundance, we observed decreases of live marine macro‐invertebrates across sequential stages of the vector from source to recipient regions. Significant differences in community composition were also observed between stages and were driven by isopods (taxonomic diversity) and isopods, amphipods and some gastropods (functional diversity). Main conclusions: The lack of management in the face of the sheer magnitude and diversity of organisms that are transported via the live marine bait trade underscores how this is an underappreciated vector that could be a considerable source of successful invasions globally.